Common practice patterns in the diagnosis and management of Vogt–Koyanagi–Harada syndrome: a survey study of uveitis specialists - Choo, Charlene H.; Acharya, Nisha R.; Shantha, Jessica G. (Frontiers in Ophthalmology, 2023)
Introduction Vogt–Koyanagi–Harada (VKH) syndrome is an inflammatory condition characterized by bilateral, granulomatous panuveitis with or without systemic manifestations, and accounts for up to 18% of referrals for panuveitis at tertiary centers in the United States of America. Despite ongoing research, there is limited evidence and no clear consensus on how to diagnose and treat patients with VKH, leading to variations in practice patterns among uveitis specialists. Methods An anonymous, online survey was distributed to uveitis specialists in the American Uveitis Society (AUS). The survey included 21 questions that asked for non-identifiable demographics and covered topics such as preferred imaging modalities, treatment for the first episode of VKH, and perceived efficacy of immunomodulatory therapy (IMT). Results A total of 104 surveys were included for analysis, representing a 38.4% response rate from the AUS listserv. A majority of respondents were uveitis fellowship trained and practiced in North America in an academic setting. Fluorescein angiography and enhanced depth imaging with optical coherence tomography were rated as the most consistently useful methods for the diagnosis of VKH. For treatment of acute initial-onset VKH, responses were divided between a preference for high-dose systemic corticosteroids with IMT (61.5%) and without IMT (37.5%). Methotrexate and mycophenolate mofetil were the most common IMTs to be used as first-line therapies, but adalimumab and infliximab were perceived to be the most effective for the treatment for VKH. Discussion While there are some common trends in the practice patterns for the diagnosis and treatment of patients with VKH, there was no clear consensus on the topic of IMT. There was a slight preference among uveitis specialists to use both IMT and systemic corticosteroids for the first episode of acute VKH.